DNA Amplification Technique for Detection of Bovine Brucellosis - Susan Maphilindawati Noor (Indonesian Center for Animal Research and Development, 2018)
Brucellosis is one of cattle diseases which causes a very significant economic loss and categorized as zoonotic disease. Early detection of Brucellosis in livestock is very important to prevent the spread of disease to livestock and humans. The success of Brucellosis control depends on rapid, sensitive and specific detection methods. The aim of this paper is to review several methods of Brucellosis detection in cattle. Currently, the detection of Brucellosis in Indonesia is using serological and isolation methods. The latter method is the gold standard of Brucellosis diagnosis, however, its sensitivity is low. Therefore, molecular techniques with DNA amplification have been developed and applied in many countries both in livestock and humans because they are more sensitive, specific and rapid in detecting Brucella sp in blood, milk and semen samples. Various DNA amplification methods for detection of Brucellosis that have been developed including polymerase chain reaction (PCR), finger printing and loop-mediated isothermal amplificatiom (LAMP). Both PCR and LAMP are more sensitive and specific in detecting Brucella sp than conventional techniques. PCR technique has advantages in detecting Brucella sp species to serotype and biovar levels. In addition, PCR reagents are cheaper and easier to obtain than LAMP eventhough, LAMP procedure is simpler and faster.